2009
DOI: 10.1002/jmri.21743
|View full text |Cite
|
Sign up to set email alerts
|

Microperfusion‐induced elevation of ADC is suppressed after contrast in breast carcinoma

Abstract: Purpose:To investigate the effect of gadolinium (Gd)-DTPA on the apparent diffusion coefficient (ADC) of breast carcinoma and to analyze the relationship between pre/postcontrast ADC and the degree of contrast enhancement. Materials and Methods:Nineteen histopathologically confirmed breast carcinomas (mean size ϭ 22 mm) were analyzed. Their ADCs before and after contrast administration were measured. The contrast-to-noise ratios (CNRs) of the tumors were measured on fat-suppressed 3D T1-weighted images in prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
66
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 31 publications
3
66
1
Order By: Relevance
“…However, in benign lesions this decrease was not significant. Yuen et al also found a decrease of the ADC value after CM application in 19 breast carcinomas [19]. In contrast to our study, Yuen et al did not have benign lesions as a control group.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…However, in benign lesions this decrease was not significant. Yuen et al also found a decrease of the ADC value after CM application in 19 breast carcinomas [19]. In contrast to our study, Yuen et al did not have benign lesions as a control group.…”
contrasting
confidence: 99%
“…The mechanism of the effect of CM on the ADC value is not yet understood. Yuen et al supposed a decrease of microperfusion due to CM which leads to a drop of the ADC value in regions with a high content of microvessels like in malignant breast tumors [19]. In our study we used b50 as the lowest b-value in order to reduce the effect of macroperfusion on the ADC value.…”
mentioning
confidence: 99%
“…This may be indirectly supported by the fact that lesions with hypervascularity tended to demonstrate low ADC values after contrast (2). Suppression of the microperfusion effect should also affect T2 signal intensity, which did not change significantly in our study, probably due to using a relatively short TR.…”
supporting
confidence: 55%
“…It was with interest that we read the article by Yuen et al (1) who reported measurable decreases in the apparent diffusion coefficient (ADC) of breast tumors following Gd contrast agent administration. The reduction was largest (34%) in lesions deemed to have particularly high vascularity.…”
mentioning
confidence: 99%
“…Additional experimentation is required before definitive conclusions regarding the mechanisms for observed ADC reductions following Gd contrast in high uptake lesions is warranted. Both T2* measurements and the use of more sophisticated diffusion sensitization schemes (4,7) would be valuable assets in furthering our understanding of the clinically relevant phenomena observed by Yuen et al (1).…”
mentioning
confidence: 99%